Analisis Faktor Faktor Terhadap Kejadian Filariasis Type Wuchereria Bancrofti, Dan Brugia Malayi Di Wilayah Kabupaten Manggarai Timur Tahun 2016 - Fransiskus Salesius Onggang (JURNAL INFO KESEHATAN, 2018)
Filariasis is a chronic infectious disease caused by filarial worms and transmitted by Mansonia, Anopheles, Culex, Armigeres mosquitoes. Living microfilariae are channeled and lymph nodes and cause inflammation of lymph node channels. This disease is one of the serious public health problems in Indonesia. Almost all regions of Indonesia are filariasis-endemic areas, especially in Eastern Indonesia which has a higher prevalence. The purpose of this study was to determine the factors associated with the incidence of filariasis in Pota District, East Manggarai Regency in 2016. The location of this study was carried out in Pota Subdistrict, East Manggarai Regency, with sampling in 4 villages conducted for approximately 2 months, namely in September to October 2016. This study used a descriptive survey method and finger blood survey to see the description of physical environmental factors and behavior of the head of the family in filariasis disease and type of microfilariae. Independent variables (free), which are included in this variable are environmental factors and behavior of the family head with indications of the physical environment (temperature, humidity, place of breeding of family mosquitoes and mosquito resting places) and the behavior of the head of the family which consists of knowledge and attitudes (knowledge of disease Filariasis: Dependent variable (bound) or variable Y which is expected to experience changes due to the influence of independent variables included in this variable is the incidence of Filariasis Disease. The population in this study were all family heads in Pota District, totaling 4570 populations, with Sampling technique is proportionally 154. Data is processed and analyzed descriptively presented in the form of frequency distribution tables of each independent variable with a 95% confidence level (α = 0.05). The results of this study indicate that the four factors include environment, work, Air humidity, per Night effects significantly have a risk of filariasis transmission (p> 0.05). Of the various species found two types of filariasis species namely Wuchereria Bancrofti and Brugia malayi. The conclusion from the results of this study can be concluded that the incidence of filariasis in Sambi Rampas subdistrict, East Manggarai Regency was caused by environmental factors, occupation, air humidity, human behavior and all blood survey samples found (100%) positive for filariasis Wuchereria Bancrofti and Brugia Malayi.